Genome-Wide Analysis Revealed Homozygosity and Demographic History of Five Chinese Sheep Breeds Adapted to Different Environments - Adam Abied (Genes, 2020)
Homozygosity of long sequence genotypes are a result of parents transmitting identical haplotypes, which can be used to estimate their auto-zygosity. Therefore, we used high-density SNP Chip data to characterize the auto-zygosity of each breed according to the occurrence and distribution of runs of homozygosity (ROH). Subsequently, we identified the genomic regions with high runs of homozygosity frequencies within individuals of each breed. We selected 96 sheep samples from five local Chinese sheep breeds belonging to different geographical locations. We identified 3046 ROHs within the study breed individuals, among which the longer segments (>1–5 Mb) were dominant. On average, ROH segments covered about 12% of the genomes; the coverage rate of OAR20 was the lowest and that of OAR2 was the highest. The distribution analysis of runs of homozygosity showed that the detected ROH mainly distributed between >26 and 28 Mb. The Hetian and Hu sheep showed the lowest ROH distribution. The estimation of homozygosity level reflects the history of modern and ancient inbreeding, which may affect the genomes of Chinese indigenous sheep breeds and indicate that some animals have experienced recent self-pollination events (Yabuyi, Karakul and Wadi). In these sheep breeds, the genomic regions were assumed to be under selection signatures frequently in line with long ROH. These regions included candidate genes associated with disease resistance traits (5S_rRNA), the innate and adaptive immune response (HERC2 and CYFIP1), digestion and metabolism (CENPJ), growth (SPP1), body size and developments (GJB2 and GJA3). This study highlighted new insights into the ROH patterns and provides a basis for future breeding and conservation strategies of Chinese sheep breeds.